The tech-prep initiative and the quality of the secondary educational experience for targeted students - Steinle, Mark R., author; Gloeckner, Gene, advisor (Colorado State University. Libraries, 2003)
The majority of the research that has been reported on the federal funding initiative, tech-prep, has been done with the administrators perceptions of what is being done and how it is affecting the students learning experience. A three-year study was conducted in Colorado (Gloeckner & Lyons, 2001) to evaluate the student's perceptions, tech-prep versus non tech-prep. This study expanded on that project looking at the tech-prep students and analyzing the data, on two independent variables, the effects of the size of the school district and the number of years of funding. The survey developed for the Colorado State University was modified to include Wyoming consortium data. Surveys were collected and analyzed for the two independent variables and for any interaction. Significant results were found in several areas. The analysis of school district of size showed significance in the assignment of a counselor, with large districts more likely to assign students to a counselor. Small schools reported to have experienced an improvement in grades and that the teachers in small schools are more likely to take time to explain assignments to the student as well as take time to instruct the students in what is required to learn and receive a passing grade in class. Students felt that the math classes as well as the communication/English/language arts classes were useful to them in their personal life. Those students that were enrolled in classes that have received funding for six or more years were more likely to be assigned to a counselor, however those enrolled in programs that had received funding for three years or less reported more frequent visits to the counselor. Those students that attended classes supported for over six years reported having better grades this year and in high school in general. Students in classes that received funding for three years or less felt that their grades had gotten better in the past two years. Students that attend classes that have received federal funding for six years or more, students reported that the use of calculators and technical journals was increased. The interaction of the two independent variables was significant in three instances. Students reported higher grades from consortia that had received funding for six or more years and being from small school districts. There were two disordinal interactions, students from large districts that had received funding for six or more years found mathematics to be more useful in their personal lives, conversely students from small districts that had received funding for six or more years found Comm/English/Language arts classes more helpful in their personal life.
Keywords: secondary education; industrial arts education